2015
DOI: 10.5897/jmpr2015.5953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracts of traditional Chinese medicines on anti-tyrosinase and antioxidant activities

Abstract: Fifty important cosmetic skin-whiting traditional Chinese medicines (TCMs) were investigated for their anti-tyrosinase and antioxidant (or DPPH-free-radical-scavenging) activities. The water and 70% ethanol extracts (WEs and 0.7EtEs, respectively) of TCMs were tested for tyrosinase inhibitory activities and DPPH-free-radical-scavenging activities. The 10 mg/ml WEs of 6 TCMs, Angelica dahurica, Anredera cordifilia Moq., Cinnamomum aromaticum, Glycyrrhiza glabra, Melia toosendan, and Prunus davidiana, presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The tyrosinase inhibitory activity of the A. niger -fermented extracts was higher than that of the unfermented extracts and the positive control, arbutin (IC 50 , 0.056 ± 0.012 mg/mL), but lower than that of kojic acid (IC 50 , 0.018 ± 0.005 mg/mL). Hsieh et al (2015) also observed a similar tendency for many traditional Chinese medicine products [34]. The DPPH radical scavenging activity and reducing power of the A. niger -fermented extracts were significantly superior to those of the control BHT (IC 50 , 1.13 ± 0.31 mg/mL) and BHT (IC 50 , 3.06 ± 0.51 mg/mL), respectively.…”
Section: Resultsmentioning
confidence: 76%
“…The tyrosinase inhibitory activity of the A. niger -fermented extracts was higher than that of the unfermented extracts and the positive control, arbutin (IC 50 , 0.056 ± 0.012 mg/mL), but lower than that of kojic acid (IC 50 , 0.018 ± 0.005 mg/mL). Hsieh et al (2015) also observed a similar tendency for many traditional Chinese medicine products [34]. The DPPH radical scavenging activity and reducing power of the A. niger -fermented extracts were significantly superior to those of the control BHT (IC 50 , 1.13 ± 0.31 mg/mL) and BHT (IC 50 , 3.06 ± 0.51 mg/mL), respectively.…”
Section: Resultsmentioning
confidence: 76%
“…Galangal can be used in various skin diseases treatment [5]. Galangal has a number of antioxidants that can protect the skin from premature aging [6]. Galangal antioxidants are able to get rid of toxins from the body and improve blood circulation [4].…”
Section: Introductionmentioning
confidence: 99%